Synergistic effect of interfacial phenomenon on enhancing catalytic performance of Pd loaded MnOx–CeO2–C hetero-nanostructure for hydrogenation and electrochemical reactions. Issue 21 (17th May 2017) - Yousaf, Ammar Bin; Imran, M.; Zaidi, Syed Javaid; Kasak, Peter; Ansari, Tariq Mahmood; Manzoor, Suryyia; Yasmeen, Ghazala
Abstract : Hetero-nanostructures have proven to be impressive materials due to their multi-functionalities in various catalytic applications. Abstract : Hetero-nanostructures have proven to be impressive materials due to their multi-functionalities in various catalytic applications. Here, the basic focus has been devoted to interface chemistry among different domains in the field of catalysis to develop an outstanding composite material with exceptional redox and catalytic properties in hydrogenation and as well in electrochemical reactions. The unique nano-hybrid material is synthesized by the loading of Pd nanoparticles onto MnO x –CeO2 mixed oxides. The heterogeneous catalytic ability for hydrogenation reactions were studied such as the reduction of organic pollutant 4-nitrophenol into 4-aminophenol and the hydrogenation of styrene into ethylbenzene. However, for electrochemical reactions, a comprehensive investigation as anode and cathode materials in direct formic acid fuel cells was performed. The strong reducing property of Pd enhanced the catalytic performance of mixed oxides and the synergistic effect of mixed oxides through interfacial phenomenon improved the performance of the hetero-nanostructured catalyst. The as-designed nanocomposite depicts high catalytic efficiency with low-cost economical standards.